Estudo da aplicabilidade de critérios morfológicos e morfométricos para a graduação de mastocitomas cutâneos em caninos - Dias, Márcia Cristiane Feltrin (2006)
Mastocitomas are most prevalent cutaneous neoplasms in canines. Aiming to study the biologic behavior of the mastocytomas, an analysis was carried through retrospect of the diagnostic of neoplasms of skin in canines, obtained from biopsies and autopsies sent to the Regional Diagnostic Laboratory (LRD) of the Federal University of Pelotas (UFPEL), between January of 1986 and December of 2005. From this revision two approaches had been carried. An epidemiologic search and another morphologic carried through the rescued diagnostic of mastocitomas in the related period. To an epidemiologic approach, 80 samples of Mastocitomas were used. It was observed that 45 (56.2%) occurred in females, 33 (41.2%) in males and in 2 (2.5%) this data was not informed. These tumors occurred in 16 different breeds. Mastocytomas predominate in animals with 6-10-years-old. Only 25 samples could be used in the morphologic and morphometric evaluation. The neoplasms were processed and histologic slides were stained by Hematoxilin-eosin, Toluidin Blue and Masson trichromic. Cellular proliferation index was inferred with AgNOR. Based on these criteria, mastocitomas were graded. Seven (28%) were classified as grade I, 11 (44%) as grade II and 7 (28%) as grade III. In the morphometric study, mast cells cellular area and perimeter were measured. In order to obtain an improvement in the graduate quality its necessary the association of morphologic and morphometric parameters.